Design and implementation of low cost wireless stethoscope - Husen, Abdurezak Tahir (2017)
Auscultation is technique which medical professions use to listen the internal body sounds such as heart and lungs sounds by using stethoscope in order to do diagnosis. But the Auscultation method is very complicated to diagnose and check the situation of the heart, this method requires to give more training to the medical professions in order acquire accurate results from heart. Furthermore, there is main problem with acoustic stethoscope which is the sound level is very low, therefore, in this project it has been designed and developed Electronic stethoscope which has capability to amplify the heart sounds and solve the main problem of the acoustic stethoscope. Therefore, this project was developed Electronic stethoscope which consist of Electret condenser microphone which pick up the heart sounds and convert to electrical signal, amplification circuit that has the ability to amplify the detected signal from heart. After amplification of the detection heart sounds it has been heard by using headphones. It also transmitted via wireless by using Bluetooth Module which has a range of wireless transmission of 30 feet. And it have lower cost compare to the wireless electronic stethoscope which currently available in the markets. Similarly, the signal has presented in a format that can make very easy to visualize and analysis by the users through Graphic user interface (GU[) using matlab software. Besides the signal can be recorded and stored for future analysis.